INNOVATIVE WAYS TO INCREASE ENERGY EFFICIENCY IN INDUSTRIAL HEATING SYSTEMS - A.Kh.Eshmamatov (SCIENCE AND INNOVATION IDEAS IN MODERN EDUCATION, 2025)
The rapid development of modern industry requires a continuous improvement of thermal processes and a rational use of energy resources. Industrial heating systems account for a significant portion of total energy consumption, and therefore, enhancing their efficiency is a key factor in sustainable development. This study explores innovative methods and technologies aimed at increasing the energy efficiency of industrial heating systems. The research emphasizes the integration of advanced heat recovery units, optimization of heat exchangers through computational fluid dynamics (CFD) analysis, and the implementation of intelligent control algorithms. Furthermore, the study discusses the application of nanofluids as high-performance heat transfer media and the utilization of waste heat for secondary energy production. The findings highlight that combining digital monitoring systems with energy-efficient materials can significantly reduce energy losses, improve process stability, and decrease operational costs. Such innovations not only contribute to reducing greenhouse gas emissions but also strengthen the economic competitiveness of industrial enterprises.